A Comprehensive Approach to Assess Occupant's Satisfaction and Performances of Residential Building - Jagadeesh Kasi; A. K. Kaliluthin (Salehan Institute of Higher Education, 2024)
This paper aims to endeavor to develop a holistic Post Occupancy Evaluation (POE) framework, amalgamating the utilization of building facilities and Building Performance Attributes (BPA) for appraising the performance of Construction and Design Firms (CDFs) alongside building performance indicators such as occupant satisfaction within residential apartment complexes. The study adopts a tripartite research methodology encompassing theoretical exploration, on-site investigations, and analytical examinations. The theoretical component entails an extensive literature survey to integrate 15 identified BPAs seamlessly. Field inquiries involve rating building performance and gauging occupant contentment. The subsequent analytical phase establishes correlations between building performance metrics and occupant satisfaction levels. This systematic approach synergizes user insights with building services, promising a rigorous and systematic building analysis. The outcomes underscore a robust correlation linking building performance attributes to occupant satisfaction, thus affirming the pivotal role of POE as an indispensable tool for appraising building performance. The analysis reveals ten highly correlated parameters, indicating a substantial 67% connection between the Building Performance Rating (BPR) and the Occupant Satisfaction Score (OSS). These influential parameters guide improvements and updates through Post-Occupancy Evaluations (POE). This process is a valuable learning tool for enhancing future organizational projects and improving building performance. The findings emphasize the pertinence of the criteria employed in evaluating building performance, which is relevant for assessing occupant contentment and CDF’s effectiveness. Comparing the previous research, this research posits the potential for widespread adoption of POE in augmenting CDFs' performance and lays the groundwork for expanding its utilization. The scholarly exploration introduces novel perspectives and paves the way for a comprehensive integration of POE to enhance CDFs' operational proficiency. Doi: 10.28991/CEJ-2024-010-02-07 Full Text: PDF